2008
DOI: 10.1029/2008jd009789
|View full text |Cite
|
Sign up to set email alerts
|

Solar modulation of Northern Hemisphere winter blocking

Abstract: [1] The blocking response to the 11-year solar cycle is investigated for 44 winters and stratified according to the level of solar activity and the phase of the Quasi-Biennial Oscillation (QBO). Several blocking features are modulated by solar activity, irrespective of the QBO phase, but the responses amplify under the QBO-west phases. Solar activity modulates the preferred locations for blocking occurrence over both Oceans, causing local frequency responses therein. Over the Pacific Ocean high/low solar acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
83
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 75 publications
(99 reference statements)
14
83
0
Order By: Relevance
“…According to these studies, enhanced solar irradiance during the 11-yr solar cycle leads to increased ultraviolet absorption by ozone and warming in the stratosphere; this warming then alters the circulation patterns in the atmosphere below. Consistently, recent works have detected a sizeable 11-yr solar signal in stratospheric (Labitzke 2005) and extratropical tropospheric circulation patterns (Kodera 2002;Baldwin and Dunkerton 2005;Woollings et al 2010), including the location and strength of blocking episodes (Barriopedro et al 2008) and NAO centers of action (Kodera 2002;Ogi et al 2003).…”
Section: Possible Mechanisms Of Centennialmentioning
confidence: 53%
“…According to these studies, enhanced solar irradiance during the 11-yr solar cycle leads to increased ultraviolet absorption by ozone and warming in the stratosphere; this warming then alters the circulation patterns in the atmosphere below. Consistently, recent works have detected a sizeable 11-yr solar signal in stratospheric (Labitzke 2005) and extratropical tropospheric circulation patterns (Kodera 2002;Baldwin and Dunkerton 2005;Woollings et al 2010), including the location and strength of blocking episodes (Barriopedro et al 2008) and NAO centers of action (Kodera 2002;Ogi et al 2003).…”
Section: Possible Mechanisms Of Centennialmentioning
confidence: 53%
“…The reduced frequency of northerly types in solar maxima is likely to be related to the weakening of the two meridional modes of variability (1st and 2nd Eurasian modes, according to the nomenclature used by Huth et al, 2006) and the change in their shapes from purely meridionally oriented wavetrains towards more zonally oriented "horseshoe-like" patterns. This is also related to the eastward shift of the maximum occurrence of atmospheric blockings over the Euro-Atlantic sector under a high solar activity by about 20 • (Barriopedro et al, 2008). The marginally significant tendency towards cyclonic types being more frequent under moderate solar activity cannot be explained in terms of changes in the modes of atmospheric circulation variability and the reason is unclear.…”
Section: Resultsmentioning
confidence: 88%
“…The circulation features so far examined in this respect include the latitudinal position of storm tracks (Brown and John, 1979;Tinsley, 1988), the position of major action centres (Christoforou and Hameed, 1997), blocking activity (Barriopedro et al, 2008), Northern and Southern annular modes (Ruzmaikin and Feynman, 2002;Ogi et al, 2003Ogi et al, , 2004Kuroda and Kodera, 2005;Huth et al, 2007), and position, intensity, and spatial extent of the North Atlantic Oscillation (Boberg and Lundstedt, 2002;Kodera, 2002Kodera, , 2003 as well as other modes of atmospheric low-frequency variability (Huth et al, 2006). The composite analysis revealed an enhanced zonality of tropospheric circulation in the mid latiCorrespondence to: R. Huth (huth@ufa.cas.cz) tudes under high solar activity Hejda, 2002, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A bootstrap test was employed, resampling the sets of winters in order to estimate the sampling uncertainty, to test whether the solar pattern in a was different from that associated with the NAO in b: this found that the two patterns are significantly different at the 93% level flow becomes south-westward around the longitude of the event centre ). Long-lived Atlantic blocking events at more eastward locations have been found to be more prevalent at sunspot minimum than at higher solar activity, and this leads to colder winters in Europe (Barriopedro et al 2008). Note, however, that to the west of the event centre warm air is drawn up from the south-west and hence if the blocking event centre moves exceptionally far to the east temperatures in western Europe may rise rather than fall: the region where CET is measured is quite close to the average longitude of blocking event centres and, although it shows a net cooling effect for lower solar activity, this is much smaller than the effect found further to the east.…”
Section: Regional Climate Effectsmentioning
confidence: 99%